Analysis of Students' Concept Understanding Using the STEM Integrated Cognitive Conflict Model - Putri Nabila; Fatni Mufit; Fuja Novitra (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the conceptual understanding and needs of teaching materials based on the STEM integrated cognitive conflict model. The study was conducted in three high schools in Padang City (SMAN 4, SMAN 9, and SMAN 11) using a survey method with a qualitative descriptive approach. Data were collected through a diagnostic test of 15 kinematics and dynamics questions, which were classified into four categories of conceptual understanding: understand, doubt, misconception, and do not know the concept. The results showed that the average student conceptual understanding was below 50%, with the highest misconception in dynamics material (41.82%) and the highest conceptual ignorance in kinematics material (51.91%). It was found that the learning approach was still teacher-centered, not encouraging active concept construction. The integration of the cognitive conflict model with the STEM approach is recommended to improve students' conceptual understanding, because it is able to stimulate cognitive reflection through conflict situations and link concepts to real-world applications. These findings indicate that the model has great potential to overcome misconceptions and build a more meaningful understanding of physics.